Una scuola che apprende - Daniela Molino (Quaderni di Sociologia, 2013)
The aim of this article is to explore differentials in student achievement related to organizational practices and management of the head teacher. After the autonomy reform, the Italian school system has undergone a slow transformation, shifting from a centralized hierarchical model to a decentralized one. At the same time, international comparative studies showed a high variance between Italian schools, but this variability is low compared to other Oecd countries. These factors suggest that there is a growing area in which head teachers, with their work and experience, can make a difference in improving the quality of education, especially student learning outcomes.In this perspective, this article firstly identifies three organizational dimensions of the Italian school system: internal collaboration, external collaboration and evaluation. Secondly, it explores the relationship between evaluation and mathematics performance. For the purposes of the article, two different databases are used: Timss 2007, which provides information about students’ learning and their socio-cultural background, and the questionnaire Invalsi Assessment System School 2006-2007.